2022
DOI: 10.3390/medicina58091212
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Tibial Component Alignment by Extramedullary System Using Simple Radiographic References in Total Knee Arthroplasty

Abstract: Background and Objectives: The tibial component alignment is an important issue for the longevity of total knee arthroplasty (TKA). The purpose of our study was to investigate the usefulness of proximal tibial references determined by pre-operative radiography and intraoperative C-arm-guided hip and ankle center marking for the extramedullary guided tibial cut in mild (<10°) and severe (≥10°) varus knee TKA. Materials and Methods: A total of 150 consecutive patients (220 cases) who underwent total knee arth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Femoral sagittal alignment with a γ angle between 0° and 3° was associated with the positive biomechanics in the finite element analyses [12, 13]. A varus or valgus coronal tibial alignment greater than 3° increases the risk of implant failure due to an imbalance in mediolateral compartmental pressure [2, 31]. Posterior tibial slope outside the range of 0–7° (≒ δ > 87 ± 3°) was associated with long‐term inferior survival [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Femoral sagittal alignment with a γ angle between 0° and 3° was associated with the positive biomechanics in the finite element analyses [12, 13]. A varus or valgus coronal tibial alignment greater than 3° increases the risk of implant failure due to an imbalance in mediolateral compartmental pressure [2, 31]. Posterior tibial slope outside the range of 0–7° (≒ δ > 87 ± 3°) was associated with long‐term inferior survival [11].…”
Section: Discussionmentioning
confidence: 99%
“…Detailed analyses of AP and lateral radiographs according to the Knee Society radiological evaluation method were performed to evaluate the positions of components in α, β, γ, and δ angles [4,26]. Postoperatively, inappropriate HKA, α, β, γ, and δ angles were defined as HKA > 0 ± 3°, α > 95 ± 3°, β > 90 ± 3°, γ > 3 ± 3°, and δ > 87 ± 3°, respectively, based on previous literatures [2,6,[11][12][13][14].…”
Section: Radiographic Evaluationmentioning
confidence: 99%
“…MPTA is one of the most common variables used to measure the severity of OA and to can be simply measured from knee radiographs. Most previous studies [28,29] have reported that MPTA is improved through surgery such as total knee arthroplasty and high tibial osteotomy. A study has reported that corrective exercises including strength and mobilization exercises will help improve MPTA and functional tasks in knee joint.…”
Section: Discussionmentioning
confidence: 99%